Synthesis and characterization of oxide nanostructures / Nurulain Binti Samat - Samat, Nurulain (2014)

(untitled)
This dissertation presents the report on a study of synthesis and characterization of oxide nanostructures. The nanostructures of SiO2 are synthesized using carbothermal reduction method. SiO2NWs formed on the silicon substrate in the variation of growth temperature and deposition time for both undoped and Cu-doped SiO2. The nanowires are then characterized by FESEM and EDX analysis. Using the same method, ZnO nanostructures are synthesized at difference growth temperature. It is found that the temperatures have changed the ZnO nanostructures from uniform crystal films to sharp ellipsoidal shape. Meanwhile, the Al-doped ZnO changed the structure into highly density ZnO nanorods. Field electron emission studies show slightly increment in the average field enhancement factor, β values if the temperature increases. The β also increases in the Al-doped ZnO nanorods. The average current did not drop when tested for about 20 minutes for all samples. ZnO nanostructures are also synthesized via sol gel method using C.Aurantifolia extracts at different concentration and pH values. The nanostructures are characterized using FESEM, XRD and PL. When the concentration of the solution increases from 0.05M to 0.20M, crystalline ZnO-NPs are fabricated. PL reveals all nanostructures emit the visible PL spectra in the range of 450-591 nm. The broad yellow band is referred to hydroxyl group, which is confirmed also in the XRD analysis. The changes in pH values also give significant effect on the formation of ZnO nanostructures. The samples show highly crystalline nanorods formed when the samples are further heated to 300ºC at longer time.